CLUSTERING: CREATING AND PROMOTING BUSSINESS SOCIAL NETWORK SUPPORTED AGRICULTURE IN THESSALONIKI - Andreas PAPANDREOU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of this paper is to investigate the creation, promotion and sustainability of a socially supported agricultural network. The recording and the theoretical co-operative strategy that can be developed by actors in the region to achieve the maximum possible growth outcomes. The methodological approach followed is based on the research of scientific approaches and scientific bibliography and aims at the overall assessment of the usefulness of such a network. As a result of this research, it is considered that proper planning and optimal use of all the data held in their hands by all the stakeholders in the network is necessary so that we have sustainability of the agro - food sector of the city and why not of the country.